Potential health benefits of combined extracts from germinated brown jasmine rice (Oryza sativa L.), Moringa oleifera leaves, and Cordyceps militaris - Pongrawee Nimnoi; Neelawan Pongsilp (CyTA - Journal of Food)
Extracts from powders of geminated brown rice (Oryza sativa L.), Moringa oleifera, and Cordyceps militaris were combined in various ratios and their health-beneficial properties were investigated. All combined extracts exerted the synergistic effects on antioxidant activity as well as inhibitions against α-amylase and α-glucosidase. Extract formulas T4 (70% germinated brown jasmine rice, 20% M. oleifera dry leaves, and 10% C. militaris) and T2 (80% germinated brown jasmine rice, 10% M. oleifera dry leaves, and 10% C. militaris) elicited the significantly highest antioxidant activity and the significantly highest inhibition against α-glucosidase, respectively. Both formulas exhibited the significantly highest inhibition against α-amylase. As compared to each other, extract formulas T4 and T2 possessed the higher glucose consumption-promoting and antiinflammatory activities, respectively. Both formulas were not toxic to normal RAW-264.7 and SW-480 human colon cancer cells. Bioactive compounds with health-supporting properties were identified using UHPLC-QTOF-MS/MS. These combined extracts can be promising therapeutic food.